Exploration on Molecular Mechanism of Reversal Effect of Compound Danshen Tablets on Hepatic Fibrosis Based on Network Pharmacology - Minling Cao; Jingyue Fan; Xiaoli Yang; Meifeng Shi; Shanshan Lin; Xiaoling Chi (Applied Bionics and Biomechanics)
Objective. To research the molecular mechanism of compound Danshen tablets in the treatment of hepatic fibrosis through network pharmacology. Methods. Traditional Chinese medicine systems pharmacology (TCMSP) and online Mendelian inheritance in man (OMIM) databases were searched for compound Danshen tablets’ active ingredients o and hepatic fibrosis-related genes. The network enrichment of the targets of “herb-compound-target” was visualized and analyzed using Cytoscape software. Then, the screened target genes were used to construct a protein-protein interaction network. The DAVID enrichment database (the database for annotation, visualization, and integrated discovery) was adopted for GO (Gene Ontology) enrichment and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment of vital nodes. Results. The results yielded 234 targets of compound Danshen tablets; ten important targets (TNF, IL-10, TGF-β1, EGF, CXCL16, CCL21, SERPINB5, SERPINA1, SOD2, and PPIG) for reversing hepatic fibrosis; and four core targets (TNF, IL-10, TGF-1, and EGF). In addition, KEGG enrichment analysis showed that compound Danshen tablets mainly involved FoxO and MAPK signaling pathways, as the key signaling pathways in the treatment of hepatic fibrosis. Conclusion. TNF, IL-10, TGF-1, and EGF and FOXO and MAPK signaling pathways play a key role in the pathogenesis of hepatic fibrosis. Based on the results of this study, the mechanism of action of compound Danshen tablets in the treatment of hepatic fibrosis may be associated with the regulation of FoxO and MAPK signaling pathways and inhibition of TNF, IL-10, TGF-1, and EGF.